2003
DOI: 10.1002/art.10974
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of nucleosomal antigens (histones and DNA) in the epidermal basement membrane in human lupus nephritis

Abstract: Objective. Antinuclear autoantibodies complexed to nucleosomes can bind to heparan sulfate (HS) in the glomerular basement membrane. This binding is due to the binding of the positively charged histones to the strongly anionic HS. Nucleosomes and histones have been identified in glomerular deposits in human lupus nephritis. We investigated whether nucleosomes are present in the basement membrane of nonlesional skin of lupus patients.Methods. Skin biopsy samples from patients with systemic lupus erythematosus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 36 publications
2
54
0
3
Order By: Relevance
“…Because antibodies eluted from nephritic B/W kidneys 30 and experimental antibodies generated in different species all recognize components of nucleosomes and stain EDDs, the nature of such EDDs is most likely reflecting released chromatin fragments complexed in vivo with autoantibodies. Similar mechanisms may be operational for binding of autoantibodies in other basement membranes, as indicated by Grootscholten et al 44 Early electron microscopy studies on lupus nephritic kidneys revealed the presence of EDDs associated with GBMs, 27 and correlation between EDDs and the clinical course of lupus nephritis has been reported. [27][28][29] These deposits have been assumed to contain chromatin constituents and could therefore represent target structures for pathogenic anti-dsDNA antibodies (Refs.…”
Section: Discussionmentioning
confidence: 85%
“…Because antibodies eluted from nephritic B/W kidneys 30 and experimental antibodies generated in different species all recognize components of nucleosomes and stain EDDs, the nature of such EDDs is most likely reflecting released chromatin fragments complexed in vivo with autoantibodies. Similar mechanisms may be operational for binding of autoantibodies in other basement membranes, as indicated by Grootscholten et al 44 Early electron microscopy studies on lupus nephritic kidneys revealed the presence of EDDs associated with GBMs, 27 and correlation between EDDs and the clinical course of lupus nephritis has been reported. [27][28][29] These deposits have been assumed to contain chromatin constituents and could therefore represent target structures for pathogenic anti-dsDNA antibodies (Refs.…”
Section: Discussionmentioning
confidence: 85%
“…It is well established that ICs are involved in many of the disease manifestations of SLE, including nephritis (3,5), pleuritis (6), vasculitis (7), skin and CNS involvement (8)(9)(10), and thrombosis (11,12). Deposited IgG or ICs cause local inflammation by activation of the classical pathway of complement with recruitment of PMNs, which could contribute to tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…ICs may also activate PMNs and induce oxidative burst (4). Many of the disease manifestations of SLE, including nephritis (3,5), pleuritis (6), vasculitis (7), and skin and central nervous system (CNS) involvement (8)(9)(10) are most likely IC mediated. Furthermore, autoantibodies against phospholipids are associated with the development of thrombosis (11,12).…”
mentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, characterized by autoantibodies and systemic clinical manifestations (9). Abnormalities in apoptosis lead to the release of DAMPs and nuclear components that stimulate the immune system to produce autoantibodies including anti-DNA Abs, activate the complement system, and damage tissues (10)(11)(12)(13)(14)(15). This process initiates a pathogenic cycle in which both the adaptive and the innate immune system collaborate to advance the disease.…”
mentioning
confidence: 99%